Wrażliwość antropologiczna i świat przedstawiony. Szkic do antropologii literatury - Burszta, Wojciech J. (Er(r)go. Teoria - Literatura - Kultura, 2009)
Anthropological Sensitivity and the World Presented. An Essay on the Anthropology of Literature Abstract in English Wojciech J. Burszta's essay takes its inspiration from two different sources: it recognises a new, modified attitude to "classical" anthropological texts by Frazer. Malinowski, Mead, Levi-Strauss or Benedict but it also centres round a theory of the literary truth developed by Mario Vargas Llosa. Llosa differentiates between the truth of non-fictional writing (e.g. history, journalism) and the truth of fiction which depends on its power to create illusions and captivate the reader's imagination. Burszta points out that the anthropological discourse is a hybrid form in that respect: it combines a commitment to facts with imaginative recreation of the world, which is characteristic of literature. Thus. according to Burszta, anthropology comes to occupy the no-man's-land in between nonfiction and fiction. Consequently, anthropological imagination will be in close rapport with aesthetic imagination which does not have to rely on the author's actual experiences. .